Implementing NEP 2020: Active Learning and Student Engagement in Engineering Education - Yadav, Jyoti; Desai, Swati; Patil, Sanyogita; Jagtap, Pratibha; Mulla, Shakil (Journal of Neonatal Surgery, 2025)
The National Education Policy (NEP) 2020 marks a significant reform in India’s educational system, championing a shift towards learner-centric pedagogies and innovative teaching methods. In the context of engineering education, this policy addresses the dual challenge of cultivating both technical expertise and essential soft skills. NEP 2020 advocates for the integration of active learning tools, such as flipped classrooms, and project-based learning (PBL), to enhance student engagement and educational outcomes. These active learning strategies aim to transition from traditional passive instruction to dynamic, participatory learning experiences. Flipped classrooms reverse conventional teaching by having students review content outside of class and apply their knowledge during class time, fostering deeper understanding and application. Project-based learning encourages students to tackle real-world problems, promoting critical thinking and problem-solving skills. This paper investigates the application of these active learning tools within engineering curricula, evaluating their effectiveness in improving student engagement and academic performance. Additionally, it examines the pivotal role of educators in implementing these strategies and underscores the necessity of ongoing teacher professional development to meet the aspirations outlined in NEP 2020. By analyzing these elements, the study aims to advance a more progressive and comprehensive approach to engineering education.